Aligned Carbon Nanotube‐Silicon Sheets: A Novel Nano‐architecture for Flexible Lithium Ion Battery Electrodes. (1st August 2013) - Fu, Kun; Yildiz, Ozkan; Bhanushali, Hardik; Wang, Yongxin; Stano, Kelly; Xue, Leigang; Zhang, Xiangwu; Bradford, Philip D.
<x xml:space="preserve">Abstract</x> Aligned carbon nanotube sheets provide an engineered scaffold for the deposition of a silicon active material for lithium ion battery anodes. The sheets are low‐density, allowing uniform deposition of silicon thin films while the alignment allows unconstrained volumetric expansion of the silicon, facilitating stable cycling performance. The flat sheet morphology is desirable for battery construction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>